The Effectiveness of Traditional Medicine of Beras Kencur Herbal Medicine on Increasing Breast Milk Production - Rita Amelia; Tetin Rismayanti (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Indonesian people have also long known and used medicinal plants to overcome various health problems, some traditional preparations such as beras kencur for breastfeeding mothers are believed to relieve disorders during breastfeeding consisting of pain and swelling of the mother, reduced breast milk and not smooth. The purpose of this study was to analyze the effectiveness of traditional herbal medicine (beras kencur) in postpartum and lactating mothers. This type of research is an experimental quasy one group pre post test. The intervention given was beras kencur herbal medicine on the quantity of breast milk production with a T-test difference test. The population and sample in this study were the number of postpartum mothers as many as 32 breastfeeding mothers. Bivariate analysis show that there is an effect of giving the extract of " beras kencur " for 7 days on increasing maternal breast milk and statistically the difference is considered significant, because the p-value is 0.001 < 0.05. Traditional herbal medicine beras kencur extract is effective in increasing breast milk production.